Evaluation of sustainability of a residential building using SVAGRIHA - a case of Mato Ghar - Adhikari, Samiksha; B. Bajracharya , Sushil (Journal of Engineering Issues and Solutions, 2024)
GRIHA, which stands for Green Rating for Integrated Habitat Assessment, is a rating system for large scale buildings. GRIHA was created to promote sustainable and eco-friendly practices in the construction and operation of buildings. GRIHA addresses various green building concepts in various phases of buildings by using five ‘R’, i.e., recycle, reuse, reduce, refuse, and reinvent, to determine and encourage the sustainability of a building via rating. SVAGRIHA is a green rating system which falls under GRIHA, which is a rating system for small scale buildings. The study presented in this paper applies SVAGRIHA framework for determining the sustainability and green rating of Mato Ghar. This study has applied case study approach and chosen Mato Ghar as a suitable case study residence, as the requirements for using SVAGRIHA framework is for buildings with built-up area less than 2500 sq.m. Results showed that sustainability of a residence will be higher if it has used energy conservation as a part of the building lifecycle, energy efficient planning and design, active and passive strategies, and locally available materials. The methodology and findings in this research can also be replicated to determine the green rating of other residential buildings within and outside Kathmandu valley by architects and engineers in the process of residential building design.